2014
DOI: 10.1002/elan.201400354
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Activated Protein C Using an Aptasensor Based on PAMAM Dendrimer Modified Pencil Graphite Electrodes

Abstract: Obwohl sich der Bereich der organischen Elektronik im Laufe der letzten Jahre erheblich weiterentwickelt hat, wird er noch immer durch die Zahl verfügbarer Materialien beschränkt. Ein weiterer Ausbau erfordert die Einführung neuartiger π‐konjugierter Rückgrate, geeignete Kandidaten hierfür werden aber nur sehr selten entdeckt. Die Einführung einer neuen Klasse konjugierter Materialien – der langen α‐Oligofurane – wurde daher vor kurzem mit großem Interesse begrüßt. α‐Oligofurane weisen viele Eigenschaften auf,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
2
5
0
1
Order By: Relevance
“…The increase in Rct value was obtained by using both electrodes; PGE and CNF-IL/PGE after 0.2 µg/mL DNA-APT immobilization onto the surfaces of these electrodes. Due to the increase in repulsion force between the negatively charged DNA-Apt and the anionic redox probe, there was an increase in Rct obtained similarly to the earlier studies [ 8 , 29 , 63 ]. However, it was observed that the increase in Rct value by CNF-IL/PGE was found higher than the one by PGE in the presence of DNA-Apt immobilization ( Figure S3 ).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The increase in Rct value was obtained by using both electrodes; PGE and CNF-IL/PGE after 0.2 µg/mL DNA-APT immobilization onto the surfaces of these electrodes. Due to the increase in repulsion force between the negatively charged DNA-Apt and the anionic redox probe, there was an increase in Rct obtained similarly to the earlier studies [ 8 , 29 , 63 ]. However, it was observed that the increase in Rct value by CNF-IL/PGE was found higher than the one by PGE in the presence of DNA-Apt immobilization ( Figure S3 ).…”
Section: Resultssupporting
confidence: 83%
“…DNA-Apt was prepared according to the information given in the literature [ 60 , 61 , 62 , 63 ]. 500 µg/mL DNA-Apt was prepared in ultrapure water and kept frozen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they have been widely used for electrochemical recognition including detection of drug, DNA and drug-DNA interaction, [37][38][39] nucleic acid hybridization, 40 miRNAs, 41 stem cells, 42 aminoacids, 43 and proteins by using the aptamerprotein interaction. 44,45 The cytostatic properties and cellular effects of novel dieneruthenium(II) complexes were studied for the human cancer cell lines MCF-7 and HT-29 and Jurkat leukemia cells by Kasper et al 35 The on-line cell based biosensor was developed to monitor a time-delayed decrease in the impedance of the cell layers. Yong et al reported a direct toxicity assessment based on chronoamperometry to detect the effect of toxic chemicals on microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…PGE (kalem grafit elektrot yüzeyi) için süksinamik asit kullanılarak yapısını değiştirdiler. Bu sayede işlevselleşmiş ikinci nesil poli (amidoamin) G2-PS dendrimer yapısına sahip tek kullanımlık elektrokimyasal DNA biyosensörü geliştirdiler [33]. Abdel-Nasser Kawde vd.…”
unclassified